src/HOL/Library/Extended_Nat.thy
author hoelzl
Tue, 12 Nov 2013 19:28:55 +0100
changeset 54416 7fb88ed6ff3c
parent 54415 eaf25431d4c4
child 54419 0c50894fc0d9
permissions -rw-r--r--
better support for enat and ereal conversions

(*  Title:      HOL/Library/Extended_Nat.thy
    Author:     David von Oheimb, TU Muenchen;  Florian Haftmann, TU Muenchen
    Contributions: David Trachtenherz, TU Muenchen
*)

header {* Extended natural numbers (i.e. with infinity) *}

theory Extended_Nat
imports Main Countable
begin

class infinity =
  fixes infinity :: "'a"

notation (xsymbols)
  infinity  ("\<infinity>")

notation (HTML output)
  infinity  ("\<infinity>")

subsection {* Type definition *}

text {*
  We extend the standard natural numbers by a special value indicating
  infinity.
*}

typedef enat = "UNIV :: nat option set" ..

text {* TODO: introduce enat as coinductive datatype, enat is just of_nat *}

definition enat :: "nat \<Rightarrow> enat" where
  "enat n = Abs_enat (Some n)"
 
instantiation enat :: infinity
begin
  definition "\<infinity> = Abs_enat None"
  instance proof qed
end

instance enat :: countable
proof
  show "\<exists>to_nat::enat \<Rightarrow> nat. inj to_nat"
    by (rule exI[of _ "to_nat \<circ> Rep_enat"]) (simp add: inj_on_def Rep_enat_inject)
qed
 
rep_datatype enat "\<infinity> :: enat"
proof -
  fix P i assume "\<And>j. P (enat j)" "P \<infinity>"
  then show "P i"
  proof induct
    case (Abs_enat y) then show ?case
      by (cases y rule: option.exhaust)
         (auto simp: enat_def infinity_enat_def)
  qed
qed (auto simp add: enat_def infinity_enat_def Abs_enat_inject)

declare [[coercion "enat::nat\<Rightarrow>enat"]]

lemmas enat2_cases = enat.exhaust[case_product enat.exhaust]
lemmas enat3_cases = enat.exhaust[case_product enat.exhaust enat.exhaust]

lemma not_infinity_eq [iff]: "(x \<noteq> \<infinity>) = (\<exists>i. x = enat i)"
  by (cases x) auto

lemma not_enat_eq [iff]: "(\<forall>y. x \<noteq> enat y) = (x = \<infinity>)"
  by (cases x) auto

primrec the_enat :: "enat \<Rightarrow> nat"
  where "the_enat (enat n) = n"


subsection {* Constructors and numbers *}

instantiation enat :: "{zero, one}"
begin

definition
  "0 = enat 0"

definition
  "1 = enat 1"

instance ..

end

definition eSuc :: "enat \<Rightarrow> enat" where
  "eSuc i = (case i of enat n \<Rightarrow> enat (Suc n) | \<infinity> \<Rightarrow> \<infinity>)"

lemma enat_0 [code_post]: "enat 0 = 0"
  by (simp add: zero_enat_def)

lemma enat_1 [code_post]: "enat 1 = 1"
  by (simp add: one_enat_def)

lemma enat_0_iff: "enat x = 0 \<longleftrightarrow> x = 0" "0 = enat x \<longleftrightarrow> x = 0"
  by (auto simp add: zero_enat_def)

lemma enat_1_iff: "enat x = 1 \<longleftrightarrow> x = 1" "1 = enat x \<longleftrightarrow> x = 1"
  by (auto simp add: one_enat_def)

lemma one_eSuc: "1 = eSuc 0"
  by (simp add: zero_enat_def one_enat_def eSuc_def)

lemma infinity_ne_i0 [simp]: "(\<infinity>::enat) \<noteq> 0"
  by (simp add: zero_enat_def)

lemma i0_ne_infinity [simp]: "0 \<noteq> (\<infinity>::enat)"
  by (simp add: zero_enat_def)

lemma zero_one_enat_neq [simp]:
  "\<not> 0 = (1\<Colon>enat)"
  "\<not> 1 = (0\<Colon>enat)"
  unfolding zero_enat_def one_enat_def by simp_all

lemma infinity_ne_i1 [simp]: "(\<infinity>::enat) \<noteq> 1"
  by (simp add: one_enat_def)

lemma i1_ne_infinity [simp]: "1 \<noteq> (\<infinity>::enat)"
  by (simp add: one_enat_def)

lemma eSuc_enat: "eSuc (enat n) = enat (Suc n)"
  by (simp add: eSuc_def)

lemma eSuc_infinity [simp]: "eSuc \<infinity> = \<infinity>"
  by (simp add: eSuc_def)

lemma eSuc_ne_0 [simp]: "eSuc n \<noteq> 0"
  by (simp add: eSuc_def zero_enat_def split: enat.splits)

lemma zero_ne_eSuc [simp]: "0 \<noteq> eSuc n"
  by (rule eSuc_ne_0 [symmetric])

lemma eSuc_inject [simp]: "eSuc m = eSuc n \<longleftrightarrow> m = n"
  by (simp add: eSuc_def split: enat.splits)

subsection {* Addition *}

instantiation enat :: comm_monoid_add
begin

definition [nitpick_simp]:
  "m + n = (case m of \<infinity> \<Rightarrow> \<infinity> | enat m \<Rightarrow> (case n of \<infinity> \<Rightarrow> \<infinity> | enat n \<Rightarrow> enat (m + n)))"

lemma plus_enat_simps [simp, code]:
  fixes q :: enat
  shows "enat m + enat n = enat (m + n)"
    and "\<infinity> + q = \<infinity>"
    and "q + \<infinity> = \<infinity>"
  by (simp_all add: plus_enat_def split: enat.splits)

instance proof
  fix n m q :: enat
  show "n + m + q = n + (m + q)"
    by (cases n m q rule: enat3_cases) auto
  show "n + m = m + n"
    by (cases n m rule: enat2_cases) auto
  show "0 + n = n"
    by (cases n) (simp_all add: zero_enat_def)
qed

end

lemma eSuc_plus_1:
  "eSuc n = n + 1"
  by (cases n) (simp_all add: eSuc_enat one_enat_def)
  
lemma plus_1_eSuc:
  "1 + q = eSuc q"
  "q + 1 = eSuc q"
  by (simp_all add: eSuc_plus_1 add_ac)

lemma iadd_Suc: "eSuc m + n = eSuc (m + n)"
  by (simp_all add: eSuc_plus_1 add_ac)

lemma iadd_Suc_right: "m + eSuc n = eSuc (m + n)"
  by (simp only: add_commute[of m] iadd_Suc)

lemma iadd_is_0: "(m + n = (0::enat)) = (m = 0 \<and> n = 0)"
  by (cases m, cases n, simp_all add: zero_enat_def)

subsection {* Multiplication *}

instantiation enat :: comm_semiring_1
begin

definition times_enat_def [nitpick_simp]:
  "m * n = (case m of \<infinity> \<Rightarrow> if n = 0 then 0 else \<infinity> | enat m \<Rightarrow>
    (case n of \<infinity> \<Rightarrow> if m = 0 then 0 else \<infinity> | enat n \<Rightarrow> enat (m * n)))"

lemma times_enat_simps [simp, code]:
  "enat m * enat n = enat (m * n)"
  "\<infinity> * \<infinity> = (\<infinity>::enat)"
  "\<infinity> * enat n = (if n = 0 then 0 else \<infinity>)"
  "enat m * \<infinity> = (if m = 0 then 0 else \<infinity>)"
  unfolding times_enat_def zero_enat_def
  by (simp_all split: enat.split)

instance proof
  fix a b c :: enat
  show "(a * b) * c = a * (b * c)"
    unfolding times_enat_def zero_enat_def
    by (simp split: enat.split)
  show "a * b = b * a"
    unfolding times_enat_def zero_enat_def
    by (simp split: enat.split)
  show "1 * a = a"
    unfolding times_enat_def zero_enat_def one_enat_def
    by (simp split: enat.split)
  show "(a + b) * c = a * c + b * c"
    unfolding times_enat_def zero_enat_def
    by (simp split: enat.split add: distrib_right)
  show "0 * a = 0"
    unfolding times_enat_def zero_enat_def
    by (simp split: enat.split)
  show "a * 0 = 0"
    unfolding times_enat_def zero_enat_def
    by (simp split: enat.split)
  show "(0::enat) \<noteq> 1"
    unfolding zero_enat_def one_enat_def
    by simp
qed

end

lemma mult_eSuc: "eSuc m * n = n + m * n"
  unfolding eSuc_plus_1 by (simp add: algebra_simps)

lemma mult_eSuc_right: "m * eSuc n = m + m * n"
  unfolding eSuc_plus_1 by (simp add: algebra_simps)

lemma of_nat_eq_enat: "of_nat n = enat n"
  apply (induct n)
  apply (simp add: enat_0)
  apply (simp add: plus_1_eSuc eSuc_enat)
  done

instance enat :: semiring_char_0 proof
  have "inj enat" by (rule injI) simp
  then show "inj (\<lambda>n. of_nat n :: enat)" by (simp add: of_nat_eq_enat)
qed

lemma imult_is_0 [simp]: "((m::enat) * n = 0) = (m = 0 \<or> n = 0)"
  by (auto simp add: times_enat_def zero_enat_def split: enat.split)

lemma imult_is_infinity: "((a::enat) * b = \<infinity>) = (a = \<infinity> \<and> b \<noteq> 0 \<or> b = \<infinity> \<and> a \<noteq> 0)"
  by (auto simp add: times_enat_def zero_enat_def split: enat.split)


subsection {* Numerals *}

lemma numeral_eq_enat:
  "numeral k = enat (numeral k)"
  using of_nat_eq_enat [of "numeral k"] by simp

lemma enat_numeral [code_abbrev]:
  "enat (numeral k) = numeral k"
  using numeral_eq_enat ..

lemma infinity_ne_numeral [simp]: "(\<infinity>::enat) \<noteq> numeral k"
  by (simp add: numeral_eq_enat)

lemma numeral_ne_infinity [simp]: "numeral k \<noteq> (\<infinity>::enat)"
  by (simp add: numeral_eq_enat)

lemma eSuc_numeral [simp]: "eSuc (numeral k) = numeral (k + Num.One)"
  by (simp only: eSuc_plus_1 numeral_plus_one)

subsection {* Subtraction *}

instantiation enat :: minus
begin

definition diff_enat_def:
"a - b = (case a of (enat x) \<Rightarrow> (case b of (enat y) \<Rightarrow> enat (x - y) | \<infinity> \<Rightarrow> 0)
          | \<infinity> \<Rightarrow> \<infinity>)"

instance ..

end

lemma idiff_enat_enat [simp, code]: "enat a - enat b = enat (a - b)"
  by (simp add: diff_enat_def)

lemma idiff_infinity [simp, code]: "\<infinity> - n = (\<infinity>::enat)"
  by (simp add: diff_enat_def)

lemma idiff_infinity_right [simp, code]: "enat a - \<infinity> = 0"
  by (simp add: diff_enat_def)

lemma idiff_0 [simp]: "(0::enat) - n = 0"
  by (cases n, simp_all add: zero_enat_def)

lemmas idiff_enat_0 [simp] = idiff_0 [unfolded zero_enat_def]

lemma idiff_0_right [simp]: "(n::enat) - 0 = n"
  by (cases n) (simp_all add: zero_enat_def)

lemmas idiff_enat_0_right [simp] = idiff_0_right [unfolded zero_enat_def]

lemma idiff_self [simp]: "n \<noteq> \<infinity> \<Longrightarrow> (n::enat) - n = 0"
  by (auto simp: zero_enat_def)

lemma eSuc_minus_eSuc [simp]: "eSuc n - eSuc m = n - m"
  by (simp add: eSuc_def split: enat.split)

lemma eSuc_minus_1 [simp]: "eSuc n - 1 = n"
  by (simp add: one_enat_def eSuc_enat[symmetric] zero_enat_def[symmetric])

(*lemmas idiff_self_eq_0_enat = idiff_self_eq_0[unfolded zero_enat_def]*)

subsection {* Ordering *}

instantiation enat :: linordered_ab_semigroup_add
begin

definition [nitpick_simp]:
  "m \<le> n = (case n of enat n1 \<Rightarrow> (case m of enat m1 \<Rightarrow> m1 \<le> n1 | \<infinity> \<Rightarrow> False)
    | \<infinity> \<Rightarrow> True)"

definition [nitpick_simp]:
  "m < n = (case m of enat m1 \<Rightarrow> (case n of enat n1 \<Rightarrow> m1 < n1 | \<infinity> \<Rightarrow> True)
    | \<infinity> \<Rightarrow> False)"

lemma enat_ord_simps [simp]:
  "enat m \<le> enat n \<longleftrightarrow> m \<le> n"
  "enat m < enat n \<longleftrightarrow> m < n"
  "q \<le> (\<infinity>::enat)"
  "q < (\<infinity>::enat) \<longleftrightarrow> q \<noteq> \<infinity>"
  "(\<infinity>::enat) \<le> q \<longleftrightarrow> q = \<infinity>"
  "(\<infinity>::enat) < q \<longleftrightarrow> False"
  by (simp_all add: less_eq_enat_def less_enat_def split: enat.splits)

lemma numeral_le_enat_iff[simp]:
  shows "numeral m \<le> enat n \<longleftrightarrow> numeral m \<le> n"
by (auto simp: numeral_eq_enat)

lemma numeral_less_enat_iff[simp]:
  shows "numeral m < enat n \<longleftrightarrow> numeral m < n"
by (auto simp: numeral_eq_enat)

lemma enat_ord_code [code]:
  "enat m \<le> enat n \<longleftrightarrow> m \<le> n"
  "enat m < enat n \<longleftrightarrow> m < n"
  "q \<le> (\<infinity>::enat) \<longleftrightarrow> True"
  "enat m < \<infinity> \<longleftrightarrow> True"
  "\<infinity> \<le> enat n \<longleftrightarrow> False"
  "(\<infinity>::enat) < q \<longleftrightarrow> False"
  by simp_all

instance by default
  (auto simp add: less_eq_enat_def less_enat_def plus_enat_def split: enat.splits)

end

instance enat :: ordered_comm_semiring
proof
  fix a b c :: enat
  assume "a \<le> b" and "0 \<le> c"
  thus "c * a \<le> c * b"
    unfolding times_enat_def less_eq_enat_def zero_enat_def
    by (simp split: enat.splits)
qed

(* BH: These equations are already proven generally for any type in
class linordered_semidom. However, enat is not in that class because
it does not have the cancellation property. Would it be worthwhile to
a generalize linordered_semidom to a new class that includes enat? *)

lemma enat_ord_number [simp]:
  "(numeral m \<Colon> enat) \<le> numeral n \<longleftrightarrow> (numeral m \<Colon> nat) \<le> numeral n"
  "(numeral m \<Colon> enat) < numeral n \<longleftrightarrow> (numeral m \<Colon> nat) < numeral n"
  by (simp_all add: numeral_eq_enat)

lemma i0_lb [simp]: "(0\<Colon>enat) \<le> n"
  by (simp add: zero_enat_def less_eq_enat_def split: enat.splits)

lemma ile0_eq [simp]: "n \<le> (0\<Colon>enat) \<longleftrightarrow> n = 0"
  by (simp add: zero_enat_def less_eq_enat_def split: enat.splits)

lemma infinity_ileE [elim!]: "\<infinity> \<le> enat m \<Longrightarrow> R"
  by (simp add: zero_enat_def less_eq_enat_def split: enat.splits)

lemma infinity_ilessE [elim!]: "\<infinity> < enat m \<Longrightarrow> R"
  by simp

lemma not_iless0 [simp]: "\<not> n < (0\<Colon>enat)"
  by (simp add: zero_enat_def less_enat_def split: enat.splits)

lemma i0_less [simp]: "(0\<Colon>enat) < n \<longleftrightarrow> n \<noteq> 0"
  by (simp add: zero_enat_def less_enat_def split: enat.splits)

lemma eSuc_ile_mono [simp]: "eSuc n \<le> eSuc m \<longleftrightarrow> n \<le> m"
  by (simp add: eSuc_def less_eq_enat_def split: enat.splits)
 
lemma eSuc_mono [simp]: "eSuc n < eSuc m \<longleftrightarrow> n < m"
  by (simp add: eSuc_def less_enat_def split: enat.splits)

lemma ile_eSuc [simp]: "n \<le> eSuc n"
  by (simp add: eSuc_def less_eq_enat_def split: enat.splits)

lemma not_eSuc_ilei0 [simp]: "\<not> eSuc n \<le> 0"
  by (simp add: zero_enat_def eSuc_def less_eq_enat_def split: enat.splits)

lemma i0_iless_eSuc [simp]: "0 < eSuc n"
  by (simp add: zero_enat_def eSuc_def less_enat_def split: enat.splits)

lemma iless_eSuc0[simp]: "(n < eSuc 0) = (n = 0)"
  by (simp add: zero_enat_def eSuc_def less_enat_def split: enat.split)

lemma ileI1: "m < n \<Longrightarrow> eSuc m \<le> n"
  by (simp add: eSuc_def less_eq_enat_def less_enat_def split: enat.splits)

lemma Suc_ile_eq: "enat (Suc m) \<le> n \<longleftrightarrow> enat m < n"
  by (cases n) auto

lemma iless_Suc_eq [simp]: "enat m < eSuc n \<longleftrightarrow> enat m \<le> n"
  by (auto simp add: eSuc_def less_enat_def split: enat.splits)

lemma imult_infinity: "(0::enat) < n \<Longrightarrow> \<infinity> * n = \<infinity>"
  by (simp add: zero_enat_def less_enat_def split: enat.splits)

lemma imult_infinity_right: "(0::enat) < n \<Longrightarrow> n * \<infinity> = \<infinity>"
  by (simp add: zero_enat_def less_enat_def split: enat.splits)

lemma enat_0_less_mult_iff: "(0 < (m::enat) * n) = (0 < m \<and> 0 < n)"
  by (simp only: i0_less imult_is_0, simp)

lemma mono_eSuc: "mono eSuc"
  by (simp add: mono_def)


lemma min_enat_simps [simp]:
  "min (enat m) (enat n) = enat (min m n)"
  "min q 0 = 0"
  "min 0 q = 0"
  "min q (\<infinity>::enat) = q"
  "min (\<infinity>::enat) q = q"
  by (auto simp add: min_def)

lemma max_enat_simps [simp]:
  "max (enat m) (enat n) = enat (max m n)"
  "max q 0 = q"
  "max 0 q = q"
  "max q \<infinity> = (\<infinity>::enat)"
  "max \<infinity> q = (\<infinity>::enat)"
  by (simp_all add: max_def)

lemma enat_ile: "n \<le> enat m \<Longrightarrow> \<exists>k. n = enat k"
  by (cases n) simp_all

lemma enat_iless: "n < enat m \<Longrightarrow> \<exists>k. n = enat k"
  by (cases n) simp_all

lemma chain_incr: "\<forall>i. \<exists>j. Y i < Y j ==> \<exists>j. enat k < Y j"
apply (induct_tac k)
 apply (simp (no_asm) only: enat_0)
 apply (fast intro: le_less_trans [OF i0_lb])
apply (erule exE)
apply (drule spec)
apply (erule exE)
apply (drule ileI1)
apply (rule eSuc_enat [THEN subst])
apply (rule exI)
apply (erule (1) le_less_trans)
done

instantiation enat :: "{order_bot, order_top}"
begin

definition bot_enat :: enat where
  "bot_enat = 0"

definition top_enat :: enat where
  "top_enat = \<infinity>"

instance proof
qed (simp_all add: bot_enat_def top_enat_def)

end

lemma finite_enat_bounded:
  assumes le_fin: "\<And>y. y \<in> A \<Longrightarrow> y \<le> enat n"
  shows "finite A"
proof (rule finite_subset)
  show "finite (enat ` {..n})" by blast

  have "A \<subseteq> {..enat n}" using le_fin by fastforce
  also have "\<dots> \<subseteq> enat ` {..n}"
    by (rule subsetI) (case_tac x, auto)
  finally show "A \<subseteq> enat ` {..n}" .
qed


subsection {* Cancellation simprocs *}

lemma enat_add_left_cancel: "a + b = a + c \<longleftrightarrow> a = (\<infinity>::enat) \<or> b = c"
  unfolding plus_enat_def by (simp split: enat.split)

lemma enat_add_left_cancel_le: "a + b \<le> a + c \<longleftrightarrow> a = (\<infinity>::enat) \<or> b \<le> c"
  unfolding plus_enat_def by (simp split: enat.split)

lemma enat_add_left_cancel_less: "a + b < a + c \<longleftrightarrow> a \<noteq> (\<infinity>::enat) \<and> b < c"
  unfolding plus_enat_def by (simp split: enat.split)

ML {*
structure Cancel_Enat_Common =
struct
  (* copied from src/HOL/Tools/nat_numeral_simprocs.ML *)
  fun find_first_t _    _ []         = raise TERM("find_first_t", [])
    | find_first_t past u (t::terms) =
          if u aconv t then (rev past @ terms)
          else find_first_t (t::past) u terms

  fun dest_summing (Const (@{const_name Groups.plus}, _) $ t $ u, ts) =
        dest_summing (t, dest_summing (u, ts))
    | dest_summing (t, ts) = t :: ts

  val mk_sum = Arith_Data.long_mk_sum
  fun dest_sum t = dest_summing (t, [])
  val find_first = find_first_t []
  val trans_tac = Numeral_Simprocs.trans_tac
  val norm_ss =
    simpset_of (put_simpset HOL_basic_ss @{context}
      addsimps @{thms add_ac add_0_left add_0_right})
  fun norm_tac ctxt = ALLGOALS (simp_tac (put_simpset norm_ss ctxt))
  fun simplify_meta_eq ctxt cancel_th th =
    Arith_Data.simplify_meta_eq [] ctxt
      ([th, cancel_th] MRS trans)
  fun mk_eq (a, b) = HOLogic.mk_Trueprop (HOLogic.mk_eq (a, b))
end

structure Eq_Enat_Cancel = ExtractCommonTermFun
(open Cancel_Enat_Common
  val mk_bal = HOLogic.mk_eq
  val dest_bal = HOLogic.dest_bin @{const_name HOL.eq} @{typ enat}
  fun simp_conv _ _ = SOME @{thm enat_add_left_cancel}
)

structure Le_Enat_Cancel = ExtractCommonTermFun
(open Cancel_Enat_Common
  val mk_bal = HOLogic.mk_binrel @{const_name Orderings.less_eq}
  val dest_bal = HOLogic.dest_bin @{const_name Orderings.less_eq} @{typ enat}
  fun simp_conv _ _ = SOME @{thm enat_add_left_cancel_le}
)

structure Less_Enat_Cancel = ExtractCommonTermFun
(open Cancel_Enat_Common
  val mk_bal = HOLogic.mk_binrel @{const_name Orderings.less}
  val dest_bal = HOLogic.dest_bin @{const_name Orderings.less} @{typ enat}
  fun simp_conv _ _ = SOME @{thm enat_add_left_cancel_less}
)
*}

simproc_setup enat_eq_cancel
  ("(l::enat) + m = n" | "(l::enat) = m + n") =
  {* fn phi => fn ctxt => fn ct => Eq_Enat_Cancel.proc ctxt (term_of ct) *}

simproc_setup enat_le_cancel
  ("(l::enat) + m \<le> n" | "(l::enat) \<le> m + n") =
  {* fn phi => fn ctxt => fn ct => Le_Enat_Cancel.proc ctxt (term_of ct) *}

simproc_setup enat_less_cancel
  ("(l::enat) + m < n" | "(l::enat) < m + n") =
  {* fn phi => fn ctxt => fn ct => Less_Enat_Cancel.proc ctxt (term_of ct) *}

text {* TODO: add regression tests for these simprocs *}

text {* TODO: add simprocs for combining and cancelling numerals *}

subsection {* Well-ordering *}

lemma less_enatE:
  "[| n < enat m; !!k. n = enat k ==> k < m ==> P |] ==> P"
by (induct n) auto

lemma less_infinityE:
  "[| n < \<infinity>; !!k. n = enat k ==> P |] ==> P"
by (induct n) auto

lemma enat_less_induct:
  assumes prem: "!!n. \<forall>m::enat. m < n --> P m ==> P n" shows "P n"
proof -
  have P_enat: "!!k. P (enat k)"
    apply (rule nat_less_induct)
    apply (rule prem, clarify)
    apply (erule less_enatE, simp)
    done
  show ?thesis
  proof (induct n)
    fix nat
    show "P (enat nat)" by (rule P_enat)
  next
    show "P \<infinity>"
      apply (rule prem, clarify)
      apply (erule less_infinityE)
      apply (simp add: P_enat)
      done
  qed
qed

instance enat :: wellorder
proof
  fix P and n
  assume hyp: "(\<And>n\<Colon>enat. (\<And>m\<Colon>enat. m < n \<Longrightarrow> P m) \<Longrightarrow> P n)"
  show "P n" by (blast intro: enat_less_induct hyp)
qed

subsection {* Complete Lattice *}

text {* TODO: enat as order topology? *}

instantiation enat :: complete_lattice
begin

definition inf_enat :: "enat \<Rightarrow> enat \<Rightarrow> enat" where
  "inf_enat \<equiv> min"

definition sup_enat :: "enat \<Rightarrow> enat \<Rightarrow> enat" where
  "sup_enat \<equiv> max"

definition Inf_enat :: "enat set \<Rightarrow> enat" where
  "Inf_enat A \<equiv> if A = {} then \<infinity> else (LEAST x. x \<in> A)"

definition Sup_enat :: "enat set \<Rightarrow> enat" where
  "Sup_enat A \<equiv> if A = {} then 0
    else if finite A then Max A
                     else \<infinity>"
instance proof
  fix x :: "enat" and A :: "enat set"
  { assume "x \<in> A" then show "Inf A \<le> x"
      unfolding Inf_enat_def by (auto intro: Least_le) }
  { assume "\<And>y. y \<in> A \<Longrightarrow> x \<le> y" then show "x \<le> Inf A"
      unfolding Inf_enat_def
      by (cases "A = {}") (auto intro: LeastI2_ex) }
  { assume "x \<in> A" then show "x \<le> Sup A"
      unfolding Sup_enat_def by (cases "finite A") auto }
  { assume "\<And>y. y \<in> A \<Longrightarrow> y \<le> x" then show "Sup A \<le> x"
      unfolding Sup_enat_def using finite_enat_bounded by auto }
qed (simp_all add:
 inf_enat_def sup_enat_def bot_enat_def top_enat_def Inf_enat_def Sup_enat_def)
end

instance enat :: complete_linorder ..

subsection {* Traditional theorem names *}

lemmas enat_defs = zero_enat_def one_enat_def eSuc_def
  plus_enat_def less_eq_enat_def less_enat_def

end